Taxing Polygamy - Samuel D. Brunson (Washington University Law Review, 2013)
The tax law treats married and unmarried taxpayers differently in several respects. Married persons, for example, can file and pay their taxes as a unified taxpayer, with rates that are different than those that apply to unmarried taxpayers. This different treatment of married persons has elicited criticism over the years. Some of the more salient criticisms include that married persons do not necessarily function as an economic unit, that joint filing discourages women from working, and that the various exclusions from the joint filing regime—including gay couples—is unfair. This Article looks at joint filing through the lens of polygamy. Polygamy stretches joint filing beyond what it can handle: while the current tax rates could accommodate same-sex couples without any substantive changes, applying the current married-filing-jointly tax brackets to polygamous taxpayers would have absurd—and often unjust— results. Polygamous marriage is not only quantitatively different than dyadic marriage—it is qualitatively different. These quantitative and qualitative differences render traditional joint filing an untenable fit. Ultimately, I conclude that changing from a joint filing system to a mandatory individual filing system that recognizes marriage for certain purposes would be the fairest and most administrable way to treat marriage. Because most commentators think, however, that eliminating joint filing will not happen in the foreseeable future, I also provide a second-best solution that would fit within the confines of the current joint filing regime.
Keywords: marriage; tax; joint filing; polygamy